Rituximab therapy in adults with steroid-dependent nephrotic syndrome - Hongzhen Zhong; Hong-Yan Li; Tianbiao Zhou; Wenjuan Weng (Archives of Medical Science, 2019)
Introduction Patients with steroid-dependent nephrotic syndrome (SDNS) suffer frequent relapse with adverse effects caused by long-term prednisolone treatment. Recently, the chimeric monoclonal antibody against the protein CD20 (rituximab – RTX) was observed to be efficacious and safe in the treatment of patients with SDNS. We summarized the scientific literature to evaluate RTX therapy in the clinical management of SDNS.